The city of Ember [compact disc, unabridged] - DuPrau, Jeanne (DuPrau, Jeanne. Ember., 2006)
In the year 241, twelve-year-old Lina trades jobs on Assignment Day to be a Messenger to run to new places in her decaying but beloved city, perhaps even to glimpse Unknown Regions.